PENGARUH PENGGUNAAN MEDIA KARTU DOMINO TERHADAP HASIL BELAJAR MATEMATIKA SISWA PADA MATERI PECAHAN DI KELAS IV UPT SPF SD INPRES BERTINGKAT KALUKU BODOA - Jannah, A.Miftahul; Sirajuddin, Sirajuddin; Gaffar, Abdul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research was motivated by the low mathematics learning outcomes of fourth-grade students in fractions at the UPT SPF (School-Based Learning Implementation Unit) of SD Inpres Bertingkat Kaluku Bodoa. This is due to the lack of engaging learning media and low student participation in the learning process. This study aims to determine the effect of using domino cards on students' mathematics learning outcomes in fractions.This study employed a quantitative, quasi-experimental method using a nonequivalent control group design. The sample size was 66 students, divided into two classes: an experimental class and a control class. Data collection was conducted through pretests and posttests. Data were analyzed using normality tests, homogeneity tests, and hypothesis testing (t-tests).The results showed a difference in learning outcomes between the experimental class using domino cards and the control class using conventional learning. The hypothesis test showed a significance value less than 0.05, therefore, H0 was rejected and H1 was accepted. Therefore, it can be concluded that the use of domino cards significantly improved students' mathematics learning outcomes in fractions.The use of domino cards can increase students' activity, interest, and understanding of the concept of fractions, so that learning becomes more interesting and effective.